The Benefits of Extension Program Area Specialization: A Look at Client Satisfaction and Outcomes - Mallory L Cotter; Glenn Israel (EDIS, 2021)
This study explores the effect of Extension program area on the perceptions of clientele regarding their overall satisfaction and benefits of services provided by Extension. Written by Mallory L. Cotter and Glenn D. Israel, and published by the UF/IFAS Department of Agricultural Education and Communication; 5 pp. https://edis.ifas.ufl.edu/wc396